Exploring the CO2 fugacity along the east coast of South America aboard the schooner Tara - L. Olivier; L. Olivier; L. Olivier; J. Boutin; G. Reverdin; C. Hunt; T. Linkowski; A. Chase; A. Chase; N. Haentjens; P. C. Junger; P. C. Junger; et al. (Earth System Science Data, 2025)
The air–sea CO2 flux in the coastal ocean is a critical component of the global carbon budget, yet it remains poorly understood due to limited data, the many sources and sinks of carbon, and their complex interactions. In August–November 2021, the Tara schooner collected over 14 000 km of CO2 fugacity (fCO2) measurements along the coast of South America, including in the Amazon River–ocean continuum (https://doi.org/10.5281/zenodo.13790064, Olivier et al., 2024a). The Amazon River and its oceanic plume exhibit complex interactions under the combined influence of many processes such as tides and bathymetry. Observations revealed a wide range of fCO2 values, from up to 3000 µatm in the river to a minimum of 42 µatm downstream of the plume, where values were notably lower than atmospheric levels. South of the estuary, the fCO2 of the North Brazil Current waters (0–9° S) exceeds 400 µatm, while along the Brazil Current (10–30° S), fCO2 is around 400 µatm and decreases with temperature and distance from the Equator. Due to its high variability in the coastal environment, in the dataset salinity emerged as the primary driver of fCO2 variability across this dynamic region. Despite strong variability, comparison with discrete samples of other carbonate parameters showed a mean difference of 2 µatm, within the range of uncertainties of the chemical formulas used for comparison. This dataset provides critical insights into the under-sampled region of the Brazilian coast, improving our understanding of coastal fCO2 dynamics and their role in the global carbon budget.